2013
DOI: 10.1016/j.surfcoat.2013.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low friction W–S–N solid lubricant coating

Abstract: W-S-N films were deposited by reactive magnetron sputtering from WS2 target in Ar/N2 atmosphere. Besides the standard evaluation of composition, structure, morphology, hardness and cohesion/adhesion, the core objective of this paper was to analyze coating tribological behavior. The chemical composition was 34 at.% N, 12 at.% O, 29 at.% W and 25 at.% S and the as-deposited films were completely amorphous. The film thickness was 2.3 µm including the approximately 300 nm thick adhesion improving titanium interlay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 36 publications
6
28
0
Order By: Relevance
“…As demonstrated in this work, amorphous W-S-N is an intricate elemental mixture, with a good supply of W and S atoms to diffuse to wherever the contact spots are found in a given point in time, allowing for easy WS 2 formation at the surface. This is in line with the reports from Gustavsson et al, who showed that after sliding, the outermost surface on a W-S-N coating with 34 at.% N consisted of well-aligned WS 2 [16]. It is highly important that the added element does not hinder the formation of a lubricating tribofilm by, for example, remaining in the contact or forming other compounds which give high friction or wear.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…As demonstrated in this work, amorphous W-S-N is an intricate elemental mixture, with a good supply of W and S atoms to diffuse to wherever the contact spots are found in a given point in time, allowing for easy WS 2 formation at the surface. This is in line with the reports from Gustavsson et al, who showed that after sliding, the outermost surface on a W-S-N coating with 34 at.% N consisted of well-aligned WS 2 [16]. It is highly important that the added element does not hinder the formation of a lubricating tribofilm by, for example, remaining in the contact or forming other compounds which give high friction or wear.…”
Section: Resultssupporting
confidence: 91%
“…For the theoretical simulations a composition of W 0.33 S 0.33 N 0.34 was chosen, similar to the N-31 film, and to W-S-N with 34 at.% of N for which ultra-low friction was observed [16]. The simulations consisted of 66 W, 66 S and 68 N atoms, giving a total of 200 atoms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rapid damage of the doped coatings was caused by their increased fragility, which resulted from the incorporation of Ti atoms into the structure between the planes formed by sulfur [30]. This phenomenon limits the sliding of the planes, thereby reducing the plasticity of the film and thus the lubricant effect; nevertheless, reports have indicated that highly beneficial tribological properties of WS 2 films can be achieved by doping them with Ti and/or other compounds [8,22,[30][31][32][33][34][35][36]. In the case of the films studied in this work, their poor tribological properties can be attributed to the low coatings thickness (507.2 nm), which leads to rapid wear and prevents the films from being able to bear sufficient load.…”
Section: Ball On Disc (Bod)mentioning
confidence: 99%